Citizen Participation in Disaster Mitigation in Serang City - Harfi Nurachman; Ujang Jamaludin (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
This study investigates the role of citizen participation in disaster mitigation efforts in Serang City, Indonesia, a region frequently affected by hydrometeorological disasters such as floods and strong winds. Using a qualitative approach with descriptive methods, the research was conducted through field studies involving residents in disaster-prone areas and the local Disaster Management Agency (BPBD). Data were collected via observation, semi-structured interviews, and documentation, then analyzed using an interactive model consisting of data reduction, display, and conclusion drawing. The results indicate that while public awareness of disaster risks is relatively high, actual participation remains sporadic and reactive. Factors such as limited disaster literacy, economic pressures, and unequal access to information hinder active involvement. Government programs aimed at promoting preparedness—such as simulations, training, and the creation of disaster-resilient villages—have been implemented but are often centralized and lack follow-up. The study finds that strengthening community-based mitigation efforts requires a shift toward more inclusive and continuous engagement strategies that integrate both structural and non-structural approaches. Enhancing institutional coordination, ensuring equitable access, and building local capacity are identified as critical elements in fostering a more proactive and resilient community.